Aetiopathology of ulcers of oral cavity and oropharynx: a cross sectional study - D., Thimmappa T.; S, Ramesh; Shetty, Hamsa S.; S., Gangadhara K. (International Journal of Research in Medical Sciences, 2017)
Background: Oral ulcers are common diseases for which patient seeks medical advice. Till date the clinical profile to diagnose the oral ulcers, management and risk of malignancy is not well established. Hence, the study has been taken up to investigate the aetiopathology of ulcers of oral cavity and oropharynx. Methods: 60 cases of ulcers of oral cavity and oropharynx were included in the study. The aetiopathology of ulcers of oral cavity and oropharynx were investigated on the basis of age, sex, duration, etiological factors, symptom Index, socioeconomic status and anatomical distribution. Values are expressed as percentages. Results: The highest incidence was found in low socioeconomic status. The lesions studied in this study were 50% of Non Specific ulcers [Short term (<3 wks) 20-67% and Long term (>3 wks) 10-33%], 15% of Aphthous ulcers, 8.3% of Traumatic Ulcers, 6.5% of Malignant ulcers, 6.5% of Dental ulcers, 3.2% of HIV infection & AIDS, 3.2% of ulcer due to T.B and 6.5% of ulcers. The majority of the cases were between the age 21-30 years constituting 35% followed by 11-12 years constituting 26.6%.d 62% of the short term ulcers, Female 38%. Conclusions: Low socioeconomic status, lack of education, bad oral hygiene, bad habits cultivated in early childhood is predisposing factors. Hence early diagnosis and prompt treatment is advised in all cases of ulcers.